DEVELOPMENT OF A VIRTUAL-BASED SKILL COMPETENCY TEST (UKK) PRACTICUM MODEL IN VOCATIONAL SCHOOLS DEPARTMENT OF COMPUTER NETWORKING ENGINEERING - Sapriadi, Sapriadi; St Munthakhabah R, Cita (Journal Peqguruang: Conference Series, 2023)
Abstract This study aims to determine: (1) the stages of developing a virtual-based UKK practicum model in the Network Computer Engineering Laboratory at SMK Negeri Labuang. (2) Development of a virtual-based UKK practicum model majoring in computer network engineering is valid, practical and effective as a result of development. The research method used is the method of research and development or Research and Development. The process of developing a virtual-based UKK practicum model refers to the ADDED development model which is a new development model resulting from descriptive analysis, critical analysis, and comparative analysis. The ADDED model stages include: (1) the Analyze stage, namely the analysis of the need for a computer / laptop as hardware, the availability of internet services, a computer laboratory while the application needs as software. (2) The Design Stage, namely the sequence or steps of making a design for the development of a practicum model, namely the required applications. (3) Development stage, namely product development in the form of a practicum model with a simulation model design specification. (4) Evaluate and Revise stage, namely steps in assessing and testing the validity, practicality, and effectiveness; (5) Dissemination and Implementation Stage, namely the process of disseminating and implementing the practicum model development. Assessment and testing is carried out by competent experts or experts, namely media and network computer techniques, while the testing is carried out through limited individual and group trials. The results of the assessment show that the development of a virtual-based UKK practicum model has fulfilled its validity by covering aspects of display, virtual and programming, the test results show that it is practical and effective. The development of the virtual-based UKK practicum model is said to be practical because it is in the very good category, it is said to be effective because the results of the evaluation carried out have met or reached the predetermined passing standard value. The development of a virtual-based UKK practicum model that was developed met the criteria of being valid, practical, and effective. For this reason, it is suggested that the virtual-based UKK practicum model can be used as a media for learning simulation for students majoring in network computer engineering in dealing with UKK SMK as well as a reference for tutors to conduct a practice orientation period, practice using practical tools. Keywords: Development, Model, Virtual UKK Practicum